COVID-19 and the Employment Gender Gap - Taiyo Fukai; Masato Ikeda; Daiji Kawaguchi; Shintaro Yamaguchi (Institute of Labor Economics (IZA), 2021)
This paper examines how the COVID-19 pandemic affected female employment in Japan. Our estimates indicate that the employment rate of married women with children decreased by 4 percentage points, while that of those without children decreased by only 1 percentage point, implying that increased childcare responsibilities caused a sharp decline in mothers' employment. Further, mothers who left or lost their jobs appear to have dropped out of the labor force even several months after school reopening. In contrast to women, the employment rate of married men with children was not affected, which hindered progress in narrowing the employment gender gap.
Keywords: D13; J13; J16; J21; 330; labor force participation; employment; gender gap; COVID-19; childcare